Cholangioscopy-guided lithotripsy in the treatment of difficult bile ducts stones – Bulgarian and Egyptian experience - Petko Karagyozov; Kamal El-Atrebi; Irina Boeva; Ivan Tishkov (Folia Medica, 2023)
﻿Introduction: Up to 10% of bile duct stones are deemed ‘difficult’ because they cannot be extracted using standard endoscopic techniques. In these situations, cholangioscopy allows for stone fragmentation under direct visual control. ﻿Aim: To evaluate the efficacy and safety of a digital single-operator cholangioscopy-guided lithotripsy in cases of difficult stones and to analyze factors related to adverse events and procedure time. ﻿Materials and methods: A retrospective review of prospective databases from two tertiary referral centers was performed, which included 38 patients with difficult bile duct stones. All of the patients had previous endoscopic retrograde cholangiopancreatographies and at least one unsuccessful surgery to remove a stone. Following the standard protocol, we performed a digital single-operator cholangioscopy-guided lithotripsy using either electrohydraulic or laser lithotripsy. The main goal was to achieve ductal clearance, which was confirmed by a negative occlusive cholangiogram. We also investigated the occurrence of complications, the factors associated with them, and the variables influencing procedure duration. ﻿Results: For the study period, 38 patients were treated with digital single-operator cholangioscopy-guided lithotripsy (33 with laser lithotripsy and 5 with electrohydraulic lithotripsy). Complete ductal clearance was achieved in 92.1% of cases, and in 78.9% of cases, it was accomplished in a single session. The average number of procedures until complete stone removal was 1.22 (1-3). The mean procedure times for electrohydraulic lithotripsy and laser lithotripsy was 83 minutes and 115 minutes, respectively. Complications, which were defined as mild, were observed in four (10.5%) patients. There was no correlation between age, size of stone, duration of the procedure and amount of saline used during lithotripsy and occurrence of complications. The presence of a stricture, barrel shaped or irregular shaped stones was associated with an increased risk of complications (p<0.05). Large stones, multiple lithiases, intrahepatic location, and failed previous EPLBD/ML were related to prolonged procedure time (p<0.05). ﻿ Conclusions: A single-operator cholangioscopy-guided lithotripsy is a highly effective and safe procedure. The presence of a distal common bile duct stricture and complex shape of stones is associated with a higher risk of procedure complications.